Fiscal Policy and Debt Management: A Narrative Review of Global Lessons - Lestari, Putri Ayu; Andika, Cruift (Indonesian Scientific Publication, 2025)
This narrative review investigates global practices and lessons learned regarding fiscal policy and public debt sustainability, aiming to identify institutional, structural, and strategic factors that influence long-term fiscal balance. The study draws upon peer-reviewed empirical studies, panel data analyses, and case studies sourced from Scopus, Google Scholar, and other academic databases, using keywords such as